Callus induction studies in various explants in different genotypes of sesame (Sesamum indicum L.): CALLUS INDUCTION STUDIES IN VARIOUS EXPLANTS IN DIFFERENT GENOTYPES OF SESAME - S RAGHU DEEPIKA; N A ANSARI (Journal of Oilseeds Research, 2014)
The goal of this study was to develop a suitable protocol for callus induction in sesame, Sesamum indicum which can be further used for regeneration studies. The experiments were carried out using three explants viz., cotyledonary leaf, hypocotyls and primary leaf at different hormonal combinations and concentrations to study callus induction. There was significant difference in the response of explants to different hormone treatments although there is no genotypic difference with regard to explants. Results showed that callus induction was significantly influenced by explants type. Hypocotyls responded well for callus induction in most of the genotypes. The callus induction frequency was significantly reduced (36.5%) when 0.2 mg BA was used along with 0.2 mg/l NAA. Replacing this hormonal combination with 2.0mg/l BA and 0.2 mg/l NAA greatly improved the callus induction frequency (51.4%).